Inosperma lijiangense sp. nov. (Inocybaceae, Agaricales) from Yunnan Province, China - Liu, Rui-Meng; Lu, Wen-Hua; Zhang, Gui-Qing; Kumla, Jaturong; Suwannarach, Nakarin; Elgorban, Abdallah M.; Alfagham, Alanoud T.; Dai, Dong-Qing; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2026)
During a field survey conducted in the mountainous regions of Shigu Village, Lijiang, Yunnan Province, China, two fungal specimens resembling Inosperma were collected. Morphological comparisons coupled with phylogenetic analyses based on the internal transcribed spacer (ITS) and the nuclear ribosomal large subunit (LSU) regions revealed that the specimen represents a novel species of Inosperma, herein described as I. lijiangense. This species is distinguished by a light reddish white to reddish brown, dry, fibrillose pileus; adnate to slightly sinuate, milk white to grayish orange lamellae; and a solid, cylindrical stipe that is slightly swollen at the base and lacks both an annulus and odor. The basidiospores are ellipsoid to ovoid, smooth, and pale yellowish brown. Phylogenetic analysis indicates that the new species, I. lijiangense, represented by specimens GMB-W1237 (holotype) and GMB-W1238 (paratype), constitutes a distinct lineage within Inosperma. A comprehensive description, accompanying illustrations, and results of the phylogenetic analysis are provided.